Women’s Monasteries of North Caucasus in Orthodox Female Asceticism from 19th to Early 20th Century - V. N. Goncharov; P. G. Nemashkalov; O. M. Kuklenko (Научный диалог)
This study contributes to the analysis of the ecclesiastical-monastic system during the Synodal period of the Russian Orthodox Church, prior to the sweeping changes brought about by the 1917 Revolution and the Civil War. It characterizes all women’s monasteries that emerged and operated in the North Caucasus during the 19th and early 20th centuries. The first female monastic community in the region was established in Mozdok in 1797, though it was short-lived. It was not until the 1840s to 1860s that women’s monasteries began to supplement the existing male monastic establishments in the North Caucasus. The study notes that subsequent legal reforms enabled the transformation of convents into monasteries. It has been determined that most women’s monasteries in the North Caucasus originated from female communities, with only a small fraction being founded as monasteries by regional authorities. The research illustrates the evolving status of women’s monasteries within society, linked to the development of female Orthodox asceticism. Through an analysis of this theme, it highlights the missionary and educational focus of provincial women’s monasteries. It has been revealed that all monasteries in the region operated on principles of communal living, sustained themselves through their own earnings and donations, had opportunities for constructing church complexes, and organized educational activities.